L-Aminoacid oxidase from bothrops leucurus venom Induces nephrotoxicity via apoptosis and necrosis - Morais, Isabel C. O.; Pereira, Gustavo J. S.; Orzáez, M.; Jorge, Roberta J. B.; Bincoletto, Claudia; Toyama, Marcos H. [UNESP]; Monteiro, Helena S. A.; Smaili, Soraya S.; Pérez-Payá, Enrique; Martins, Alice M. C. (Public Library Science, 2015)
Acute renal failure is a common complication caused by Bothrops viper envenomation. In this study, the nefrotoxicity of a main component of B. leucurus venom called L-aminoacid oxidase (LAAO-Bl) was evaluated by using tubular epithelial cell lines MDCK and HK-2 and perfused kidney from rats. LAAO-Bl exhibited cytotoxicity, inducing apoptosis and necrosis in MDCK and HK-2 cell lines in a concentration-dependent manner. MDCK apoptosis induction was accompanied by Ca2+ release from the endoplasmic reticulum, reactive oxygen species (ROS) generation and mitochondrial dysfunction with enhanced expression of Bax protein levels. LAAO-Bl induced caspase-3 and caspase-7 activation in both cell lines. LAAO-Bl (10 μg/mL) exerts significant effects on the isolated kidney perfusion increasing perfusion pressure and urinary flow and decreasing the glomerular filtration rate and sodium, potassium and chloride tubular transport. Taken together our results suggest that LAAO-Bl is responsible for the nephrotoxicity observed in the envenomation by snakebites. Moreover, the cytotoxic of LAAO-Bl to renal epithelial cells might be responsible, at least in part, for the nephrotoxicity observed in isolated kidney.